Application of Personal Information Cash Flow (APIC) - Based Financial Practice Innovation as a Pillar of Financial Education - Sunitha Devi; Putu Eka Dianita Marvilianti Dewi; Lucy Sri Musmini (The Indonesian Journal of Accounting Research, 2021)
This research was conducted to prove that APIC-based financial learning practices can improve financial literacy, which also has a positive effect on inclusive financial management education. The grand theory used in this research is Behavioral Finance Theory. The sample of this research used an error rate of 5%; therefore, the sample obtained amounted to 347 people. This study used the design of R&D and also the design of media applications. The study was conducted using a mixed-method. Data analysis techniques used: 1) data eligibility test, 2) t-test through one-way ANOVA analysis and 3) simple regression. The results showed that: (a) the APIC work system that was developed had met the material and media validity requirements, (b) APIC-based financial learning practices were able to increase financial literacy, and (c) APIC-based financial literacy had a positive effect on the level of inclusive financial management.